Strategi Pencegahan Pembiayaan Bermasalah pada BPRS di Kabupaten Bogor - Aulia Nur Cahyani; Neneng Hasanah; Mohammad Iqbal Irfany (AL-MUZARA'AH, 2020)
Financing is channeling funds carried out by Islamic banks, such as Islamic rural banks (BPRS). Risk arising from financing is default risk assessed by the ratio of Non Performing Financing (NPF). BPRS in the area of Kabupaten Bogor have NPF values above the safe limit set by Bank Indonesia. The purpose of this study is to identify the causes and solutions of default financing and formulate strategies for preventing default financing of BPRS in Kabupaten Bogor. The method used in this study is Analytic Network Process (ANP). The total respondents in this study are five. The result showed that external cause is the most influential factor towards the occurrence of default financing. The most influential external cause is customer's bad intention. External solution is the priority solution that need special attention. The priority external solution is strengthening the analysis. The most influential internal cause is adverse selection. Internal solution that is prioritized is training for finance officers. The priority of the default financing prevention strategy in this study is formulating financing risk mitigation.